INTRUSIVE-MAGMATIC COMPLEXES OF WILHELM ARCHIPELAGO, WEST ANTARCTICA (PART 1 – INTRUSIONS OF GABBROIDS, DIORITES AND GRANITOIDS) - Mytrokhyn, O.; Bakhmutov, V.; Аleksieienko, А.; Mytrokhina, T.; Marushchenko, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Wilhelm Archipelago and the adjacent coast of Graham Land are typical areas of calc-alkaline magmatism associated with the protracted evolution of the Antarctic Peninsula igneous belt. The authors studied intrusive complexes of the Wilhelm Archipelago (WA) in order to characterize their geographical distribution, geological occurrence and age, mineralogical and petrographical features. Geological surveys revealed that gabbro, diorite, and granitoid intrusions are widespread on the WA. Due to the processes of tectonic uplift and exhumation, both apical and bottom parts of individual intrusive bodies can be exposed on the modern erosion level. Recent geological observations have shown that plutons of different ages intersect each other in a complex sequence. This made it possible to determine their relative geological age and reconstruct the general direction of the deep magmatic development from the Early Cretaceous to the Early Paleogene, inclusive. It has been proved that the oldest massifs of gabbroids are parts of much larger intrusive bodies. They were formed in the period between the Jurassic and the Early Cretaceous periods. Crystallization differentiation of basaltic magmas gave them various scale layering. In the bottom parts of gabroid intrusions there were conditions for the formation of Fe-Ti-V and Cu-Ni-EPG mineralization. Diorite and granitoid intrusions occupy much larger areas compared to gabbroids. The formation of diorite intrusions took place in the period between the Early Cretaceous and the Paleocene. Although the oldest gabbroids were formed much earlier than diorites, the phenomena of magmatic mingling in the latter indicate that magmas of basic and intermediate composition could also synchronously intrude in common magmatic chambers. Granitoid magmatism on the WA covers the Late Cretaceous and the Paleogene periods. Most granitoid intrusions formed in the Paleocene after the main phase of tectonic deformations. Cu-Mo mineralization may be associated with these intrusions.
Keywords: geology; calc-alkaline magmatism; Antarctic Peninsula